Synthesis, structure, and in vitro antigastric cancer activity evaluation of two new Zn(II) and Cd(II)-organic frameworks. Issue 11 (3rd June 2019) - Chen, Zongnan; Zhang, Shupeng; Shao, Jianping; Su, Feng
Abstract: This article describes the synthesis and characterization of two MOFs, [Zn(L)(DMA)]n (1 ) and [Cd(L)(EtOH)2 ]n (2 ) (DMA = N, N '-dimethylacetamide, EtOH = ethanol), with different interpenetrated motifs which have been synthesized under solvothermal conditions by using a trigonal heterofunctional ligand 4, 4′-(4, 4′-bipyridine-2, 6-diyl) dibenzoic acid (H2 L). Structural analysis results via the X-ray crystal study reveal that1 features a three-dimensional (3-D) fourfold interpenetrated SrS2 -type topological framework and2 features a 3-D twofold interpenetrated ThSi2 -type topological framework. Our results show that the metal ion plays an important role in the final conformations of the resulting MOF. Furthermore, hand grinding of1 and2 without using any solvent or chemicals leads to lowering the size to the nano regime, and2 is superior to1 in terms of cytotoxicity on human gastric cancer cells (MGC-803, SGC-790, and AGS) as revealed via the MTT assay. The cytotoxicity results indicated2 showed superior activity on human gastric cancer cells AGS viability compared with1 . The apoptosis and ROS assays revealed that the compounds could induce AGS cell apoptosis and ROS accumulation;2 exhibits stronger inducing effect than1 . Abstract :